The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.4049/jimmunol.177.7.4861
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil-Derived Cationic Proteins Activate the Synthesis of Remodeling Factors by Airway Epithelial Cells

Abstract: Eosinophil cationic proteins influence several biological functions of the respiratory epithelium, yet their direct contribution to airway remodeling has not been established. We show that incubation of the human bronchial epithelial cell line, BEAS-2B, or primary cultured human bronchial epithelial cells, normal human bronchial epithelial cells, with subcytotoxic concentrations (0.1, 0.3, and 1 μM) of major basic protein (MBP), or eosinophil peroxidase (EPO), augmented the transcripts of endothelin-1, TGF-α, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 74 publications
1
79
0
1
Order By: Relevance
“…The level of sputum eosinophil plays an important role in airway remodeling in asthma (Pegorier et al 2006). Furthermore, eosinophil has been known to play a key role in the natural exacerbation caused by viral and non-viral agents in asthma (Hogan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The level of sputum eosinophil plays an important role in airway remodeling in asthma (Pegorier et al 2006). Furthermore, eosinophil has been known to play a key role in the natural exacerbation caused by viral and non-viral agents in asthma (Hogan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Both the ECP and EPO reflect the disease activity in AR, and a study reported that the ECP and EPO were predictors of the development of asthma in AR patients (Nielsen et al 2009). One study has reported that the MBP and EPO were associated with the activation of the airway remodeling factor (Pegorier et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of the transcripts encoding ChTRase were assessed by quantitative real-time PCR (Mx 3000P apparatus, Stratagene Europe, Amsterdam, The Netherlands), and their expression was normalized to that of ubiquitin C, using GeNorm software. 17 Primers (ChTRase, GenBank Identifier NM_003465, sense 5Ј-CTGCATCATGGTGCG-GTC-3Ј, antisense, 5Ј-GTGCTCAGCTGGTGGTTG-3Ј; ubiquitin C (GenBank Idenfier NM_004168), sense, 5Ј-CACTTGGTCCTGCGCTTGA-3Ј, antisense, 5Ј-TTTTGG-GAATGCAACAACTTT-3Ј) were designed using Primer Express 2 Software (Applied Biosystems, Framingham, MA) and were synthesized by Genosys (Sigma). Their sequences were blasted against Basic Local Alignment Search Tool database (http://www.ncbi.nlm.nih.gov/ BLAST).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%